2019
DOI: 10.2196/jmir.9240
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Personalized Motivational Messages by a Virtual Agent that Assists in Post-Traumatic Stress Disorder Therapy

Abstract: Background Systems incorporating virtual agents can play a major role in electronic-mental (e-mental) health care, as barriers to care still prevent some patients from receiving the help they need. To properly assist the users of these systems, a virtual agent needs to promote motivation. This can be done by offering motivational messages. Objective The objective of this study was two-fold. The first was to build a motivational message system for a virtual agent assisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 51 publications
2
39
0
1
Order By: Relevance
“…Based on our findings, the communication media used to administer internet-facilitated interventions to patients can be classified into three categories: web apps, mobile apps, and computer games. A significant number of the included studies were based on web apps [ 11 , 14 , 24 , 39 , 43 , 49 , 50 , 52 , 54 , 56 , 63 ], followed by mobile apps [ 13 , 32 , 41 , 49 , 50 , 55 , 60 , 61 ] and a game-based intervention [ 53 ]. There was only one paper that applied both web and mobile technologies for internet-based intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our findings, the communication media used to administer internet-facilitated interventions to patients can be classified into three categories: web apps, mobile apps, and computer games. A significant number of the included studies were based on web apps [ 11 , 14 , 24 , 39 , 43 , 49 , 50 , 52 , 54 , 56 , 63 ], followed by mobile apps [ 13 , 32 , 41 , 49 , 50 , 55 , 60 , 61 ] and a game-based intervention [ 53 ]. There was only one paper that applied both web and mobile technologies for internet-based intervention.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, experts were asked to provide mo tivational statements for imaginary patients who had a specific type of symptom progression and a specifi c level of trust in a good therapy outcome. 8 Using this input, a motivational system, capable of generating personalized messages, was built. A recent study showed that moti vational messages can improve reported motivation and trust, and that personalized motivational messages are particularly important in situations where symptoms initially worsen.…”
Section: Virtual Coachingmentioning
confidence: 99%
“…A recent study showed that moti vational messages can improve reported motivation and trust, and that personalized motivational messages are particularly important in situations where symptoms initially worsen. 8 The three studies discussed demonstrate how a virtual agent can inform, assist and motivate patients during home-based, online treatment of PTSD. Th e multi-model memory restructuring system (3MR) is one version of a home therapy system involving a virtual agent.…”
Section: Virtual Coachingmentioning
confidence: 99%
“…Dentre as preocupações, estão as informações fornecidas pelo paciente para o agente durante a intervenção, que consequentemente poderiam revelar suas tendências suicidas, que não são aderentes a medicamentos, e que abusam de substâncias [8]. No trabalho de Tielman, Neerincx e Brinkman [17], os autores apresentaram o projeto e a avaliação de mensagens motivacionais personalizadas para a terapia de Transtorno de Estresse Pós-Traumático (TEPT). No design participativo do agente, para cada caso, pedia-se ao especialista que escrevesse o que eles diriam ao paciente para aumentar sua motivação para continuar no tratamento.…”
Section: Design Participativo Dos Diálogosunclassified